Understanding the adoption of grazing practices in German dairy farming. (September 2018) - Schaak, Henning; Mußhoff, Oliver
Abstract: Due to a simultaneous decline in agricultural practice and an increased favorability and demand by society, grazing based milk production has become a topic of heightened interest in European agricultural policy, as well as dairy product marketing. This paper studies the behavior of German farmers with respect to the adoption of grazing practices. To do so, a structural equation model based on the technology acceptance model (TAM) is developed. Generally, the TAM hypothesizes that the perceived usefulness and the perceived ease of use are key determinants of the intention to use and the actual usage behavior of a technology. The results indicate that the perceived usefulness and perceived ease of use statistically significantly influence the adoption of grazing practices. Other important aspects are the production limitations on the individual farm, and the farmers' subjective norm towards grazing. Furthermore, the analysis reveals differences between conventional and organic farmers, showing that the influence of farmers' beliefs on the usage behavior tends to be greater for conventional farmers. The results show that farmers' subjective norm influences multiple other constructs of the model, including the intention to use. Under the assumption that farmers' perceptions of societal expectations depend on the public discourse, this indicates the relevance of public information and communication for the farmer's decision-making processes. Highlights: The technology acceptance model is applied on the adoption of grazing practices of German dairy farmers. The model is used to explain the farmer's usage behavior. The farmer's perceived ease of use and perceived usefulness of grazing influences the intention to use. We find differences between conventional and organic farmers. The farmer's perception of societal expectations influences the other beliefs and intentions in the model-".